APPLYING AN INTEGRATED TECHNOLOGY WITH A GENRE-BASED APPROACH TO WRITING LEARNING - Tampubolon, Ditanti Argadin; Samsi, Yogi Setia; Pujiawati, Nia (IKIP Siliwangi, 2024)
This research explores integrating technology with the Genre-Based Approach (GBA) in teaching writing to Vocational High School (VHS) students in Karawang, Indonesia. The research is motivated by recognizing that writing is an essential yet challenging skill for students, especially in academic and professional contexts. The Genre-Based Approach (GBA) is highlighted as a promising method to address this challenge. In addition, integrating technology, such as Microsoft PowerPoint and Google Classroom, is proposed to increase students' motivation in the learning process. This qualitative research utilizes a multiple case study design involving observation and semi-structured interviews with teachers and students. The findings showed that implementing technology-integrated GBA significantly improved students' engagement and writing skills. However, challenges such as internet access and the need for professional development for the teachers were also identified. In conclusion, this study underscores the potential of the Technology-Integrated Genre-Based Approach to improve writing instruction in vocational high schools. It calls for further research to develop strategies to address the identified challenges. Continuous professional development for teachers is essential to sustain the effective implementation of this approach. The findings can potentially inform educators, students, and schools about effective implementation strategies to improve learning outcomes.